Sustainable Tourism in Heritage Towns: A Case Study of Bandipur, Nepal - Pradhan, Asutosh (Samriddhi Journal of Development Studies, 2025)
Heritage towns are repositories of culture, history, and architecture, attracting tourists globally. However, tourism development can create challenges related to cultural preservation, environmental sustainability, and local community well-being. This study examines sustainable tourism practices in Bandipur, a heritage hill town in mid-western Nepal, emphasizing the integration of heritage conservation, community participation, eco-tourism initiatives, and economic development. Using qualitative methods, including semi-structured interviews, participant observation, and document analysis, the study identifies key strategies adopted by the local community and governance bodies to balance tourism growth with sustainability. Findings indicate that Bandipur has successfully implemented heritage restoration, eco-tourism programs, regulated cultural events, and environmental management practices. Nevertheless, challenges such as tourism pressure, cultural commodification, and resource constraints remain. The study highlights policy recommendations and strategies that can guide other heritage towns toward sustainable tourism development.